Analisis Evaluasi Akuntabilitas Pengelolaan APBDes dalam Mendukung Pemberdayaan Masyarakat di Desa Bandung Tahun 2024 - Ratu Majidah Qonitah; Laeli Nur Khanifah; Ajeng Roro Syanti; Inashaqi Salamah; Alifah Azahra Yamin (Pusat Riset dan Inovasi Nasional, 2025)
Bandung Village has strong economic potential through the development of local handicraft business units and Village-Owned Enterprises (BUMDes), but in its financial management the village experienced a decline in Village Original Revenue (PADes) from IDR 100 million in 2023 to IDR 93 million in 2024. The decline in PADes is an important indicator that reflects possible inefficiencies or weaknesses in aspects of governance, particularly accountability. This paper aims to capture an evaluation of the accountability of the use of APBDes in Bandung Village, Banjar Sub-district, Pandeglang Regency in managing its budget. With a focus on its impact on the effectiveness of community empowerment. The research method used is a qualitative method with a case study approach. The research was conducted in Bandung Village, Banjar Sub-district, Pandeglang Regency, Banten Province. Data was collected through interviews, observations, literature studies, and documentation using Policy Evaluation theory and Accountability theory. The results showed that from the analysis using evaluation theory, there were indicators that had not been met, namely adequacy and equity due to limited resources, namely funds provided by the central government. However, the analysis using accountability theory has fulfilled all indicators due to the strong commitment of the village government to advance the village. This accountability can be seen through reports on each program outcome and evidence of content uploaded on social media such as TikTok and Instagram.